Breastfeeding Experiences and Milk Production in Mothers of Multiple Birth Infants - Muja A. Gama; Ashleigh H. Warden; Jacki L. McEachran; Demelza J. Ireland; Donna T. Geddes; Sharon L. Perrella; Zoya Gridneva (Proceedings)
Breastfeeding multiple birth infants (MBIs) presents unique challenges that require tailored support and guidance, yet little research has focused on MBIs mothers experiences [...]